2004
DOI: 10.1002/pbc.20164
|View full text |Cite
|
Sign up to set email alerts
|

Methemoglobinemia in children with acute lymphoblastic leukemia (ALL) receiving dapsone forpneumocystis carinii pneumonia (PCP) prophylaxis: A correlation with cytochrome b5 reductase (Cb5R) enzyme levels

Abstract: Heterozygosity for Cb5R deficiency may pre-dispose to methemoglobinemia even on a thrice-weekly regimen of dapsone. Such individuals should avoid subsequent exposure to oxidant agents, if possible. Children with ALL tend to be symptomatic at low levels of metHb and may have delayed detection of methemoglobinemia. Hence, frequent monitoring of patients receiving dapsone is recommended. Monitoring guidelines for dapsone prophylaxis are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 42 publications
3
31
1
Order By: Relevance
“…Our prevalence of confirmed methemoglobinemia cases approaches 20%, which is higher than what has been reported in the adult literature 3, but consistent with a rate of 20% previously observed in a much smaller cohort (N = 15) of pediatric oncology patients 4.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our prevalence of confirmed methemoglobinemia cases approaches 20%, which is higher than what has been reported in the adult literature 3, but consistent with a rate of 20% previously observed in a much smaller cohort (N = 15) of pediatric oncology patients 4.…”
Section: Discussionsupporting
confidence: 92%
“…Twenty patients were required in each group to achieve 90% power. However, since the data by Williams demonstrated that mean difference in CYB5RA was 3.9 based on a small sample size (10 patients), we estimated the difference conservatively 4. Sample size computation was performed using PS software 11.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In large series, 5.8–20% of patients taking dapsone developed an increase in methemoglobinemia levels [13, 14]. Patients most at risk for dapsone-induced methemoglobinemia include anemic patients and the elderly, both of whom are frequently seen in neuro-oncology practice.…”
Section: Discussionmentioning
confidence: 99%